GAYA KEPEMIMPINAN MAHASISWA: Studi kasus Himpunan Mahasiswa Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Alauddin Makassar - Muhammad Yahya; Nursinta; Nurul Annisa; Sahrul (Department of Islamic Education Management, 2022)
This research is about the leadership style of the Student Association of the Departement of Islamic Education Management Faculty of Tarbiyah and Teacher Taraining at UIN Alauddin Makassar. The purpose of this Study was to determine the leadership style applied by the students of the Departemen of Student Association. The research method used by the resesarcher is a qualitatifve research method with a case study approach. Data collection techniques used in this studi were : documentation, interviews, observations and participants. The data analysis techniques used are: category collection, direct interpretation and case survey (secondary cross-case analysis). The results of this study are the leadership style applied by students for the 2019-2021 period. So it was found that there were differences in the student leadership model applied at the HMJ. The differences in the model in question are charismatic, democratic, authoritarian, and conditioning leadership. The leadership style of a leader has an influence on the motivation and performance of its members. In decision-making a leader is influenced by the leadership style he adheres to, if he is democratic then he respects the opinions of his members. otherwise a leader who is authoritarian style, then he will bear the burden alone.